New records of two species of Toxotrypana (Diptera: Tephritidae) in Argentina - Bertolaccini, Isabel; Castro, Damian; Curis, María Cecilia; Zucchi, Roberto A. (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2017)
In this study are disclosed new records that extend the geographical distribution of Toxotrypana australis Blanchard and T. nigra Blanchard, in Argentina.